Bioassay-guided isolation, identification of compounds from Origanum rotundifolium and investigation of their antiproliferative and antioxidant activities. - ERENLER, R; MERAL, B; SEN, O; ELMASTAS, M; AYDIN, A; EMINAGAOGLU, O; Topcu, GÜLAÇTI; TOPÇU, GÜLAÇTI (My University, 2017)
Context: Origanum (Lamiaceae) has been used in food and pharmaceutical industries. Objective: Isolation and identification of bioactive compounds from Origanum rotundifolium Boiss. and investigation of their antiproliferative and antioxidant activities. Materials and methods: The aerial part of O. rotundifolium was dried and powdered (1.0 kg ±2.0 g) then extracted with hexane, ethyl acetate, methanol and water. Solvent (3 × 1 L) was used for each extraction for a week at room temperature. The aqueous extract was partitioned with ethyl acetate (3 × 1 L) to yield the water/EtOAc extract subjected to chromatography to isolate the active compounds. The structures of isolated compounds were elucidated by 1 D, 2 D NMR and LC-TOF/MS. Results: Apigenin (1), ferulic acid (2), vitexin (3), caprolactam (4), rosmarinic acid (5), and globoidnan A (6) were isolated and identified. Globoidnan A (6), vitexin (3), and rosmarinic acid (5) revealed the excellent DPPH• scavenging effect with IC50 values of 22.4, 31.4, 47.2 μM, respectively. Vitexin (3) (IC50 3.6), globoidnan A (6) (IC50 4.6), apigenin (1) (IC50 8.9) and ferulic acid (2) exhibited more ABTS•+ activity than standard Trolox (IC50 13.8 μg/mL). Vitexin (3) revealed the most antiproliferative activity against HeLa, HT29, C6 and Vero cells lines with IC50 values of 35.6, 32.5, 41.6, 46.7 (μM), respectively. Discussion and conclusion: Globoidnan A (6) has the most antioxidant effects on all assays. This has to do with the chemical structure of the compound bearing the acidic protons. Vitexin (3) could be a promising anticancer agent.